EP 71. Single cell firing patterns in the anterior nucleus of the thalamus relate to therapy response in deep brain stimulation for refractory epilepsy. Issue 9 (September 2016) - Schaper, F.; Zhao, Y.; Wagner, L.; Colon, A.; van Kranen-Mastenbroek, V.; Gommer, E.; Janssen, M.; Ackermans, L.; van Wezel, R.; Temel, Y.; Heida, T.; Rouhl, R.
Abstract : Introduction: Patients with medically refractory epilepsy treated with deep brain stimulation (DBS) of the anterior nucleus of the thalamus (ANT) vary highly in their therapy response. Proper positioning of the DBS lead is crucial to maximize efficacy and minimize side effects. For a correct implantation, the ANT is anatomically located using pre-operative 3T MRI and perioperative microelectrode recordings (MER). Neurons in the ANT have highly variable, yet characteristic patterns of firing in bursts. During DBS lead implantation, we noted differences among patients' characteristic burst patterns along the electrode trajectory. In this study, we investigate whether electrophysiological characteristics of the target region could predict therapy response to DBS and could thus be used to improve ANT targeting during DBS surgery. Objectives: To determine whether perioperative neurophysiological characteristics relate to therapy response in DBS for patients with medically refractory epilepsy. Patients and methods: We included ten consecutive epilepsy patients planned for DBS surgery at Maastricht University Medical Center. All patients were diagnosed with medically refractory epilepsy and had incapacitating seizures. Patients failed trials of at least two reasonably tolerated and adequately chosen antiepileptic drug schedules. Using pre-operative 3T MRI, we planned an extraventricular approach to target. The ANT was defined as a grey matter structure at the top of the mamillothalamic tract. Along this trajectory, we performed stereotactic single cell MERs. The anatomical location of the recordings were verified using preoperative 3T MR images. We compared characteristics of the neural signals at different depths along the trajectory between DBS responders and non-responders. Responders were defined as patients with a seizure frequency reduction of more than 50% at one year follow-up. Results: Using MER data from 19 electrode trajectories of ten patients (one unilateral and nine bilateral trajectories), we found high-amplitude neuronal bursts around the target area or ANT. Responders to DBS ( n  = 5) had higher normalized mean firing rates and mean burst rates near the target area compared to non-responders ( n  = 5), with a clearer delineation between the target region and surroundings. Electrode trajectories and lead localization did not differ between responders and non-responders. Conclusion: Single cell firing patterns in the ANT relate to therapy response in DBS for patients with medically refractory epilepsy. Analysis of single cell firing patterns using MER may guide targeting or contribute to predicting therapy response to ANT DBS. Further exploration into the use of electrophysiological recordings is warranted to improve targeting or predict outcome in DBS for epilepsy patients.